(untitled) (Latakia University Journal -Biological Sciences Series, 2017)
نظراً إلى كفاءة الطحالب في عملية التركيب الضوئي وإنتاج الكربوهيدرات ذات القيمة الغذائية والصناعية فقد أُجري هذا البحث بهدف دراسة كمية الكربوهيدرات ونوعيتها في النوعChlorella vulgaris المعزول من المياه العذبة في جنوب سورية، وتحديد مدى تَأثُّرها باختلاف درجة الحرارة (15، 25، 35 س°) وتركيز نترات الصوديوم (0.1، 0.25، 0.4 غ/ل) وقيم pH(6، 7، 8) خلال النمو. أوضحت النتائج أن كمية الكربوهيدرات الكلية ضمن ظروف النمو المختلفة تراوحت بين 20% و40%، وكان للغالاكتوز والرامنوز السيادة على باقي السكريات. كما تبين أن درجة الحرارة (15 س◦) هي الأفضل للحصول على أكبر كمية من الكربوهيدرات بأعلى نسبة من النشا والسليلوز والهيميسليلوز والبكتين. وحقق التركيز المنخفض0.1غ/ل من نترات الصوديوم أكبر كمية من الكربوهيدرات بأعلى محتوى من البكتين ومركباته، ولميتأثر محتوى الكتلة الحيوية من الغلوكوز بنسبة النتروجين في وسط النمو. كان الوسط الحمضي هو الأفضل للحصول على أكبر كمية من الكربوهيدرات بينماازدادت نسبة السليلوز والنشا والبكتين في الوسط القلوي على حساب باقي المركبات. According to the algae ability in photosynthesis and carbohydrate production with high value in nutrition and industry, this research was carried out during 2015 to study the qualitative and quantitative content of carbohydrates in Chlorella vulgaris which was isolated from southern Syrian fresh water, and to determine the effect of the growth conditions; temperature (15, 25, 35 C), sodium nitrate concentration (0.1, 0.25, 0.4 g/l) and pH (6, 7, 8) on that content. The results showed that the total content was in the range of 20% to 40%;with galactose and rhamnose dominating among the rest of sugars. The temperature 15°C was the best to get the greatest total content with the highest value of starch, cellulose, hemicellulose and pectin. In addition, the low nitrate concentration 0.1 g/l was combined with the highest content of pectin and its compounds, while the glucose content was not affected by the nitrogen concentration. Related to pH effect, the acidic media was proved to be the best for the highest carbohydrate content. Moreover, cellulose, starch, and pectin increased in the alkali medium over the rest of carbohydrates.